2017
DOI: 10.1111/sjop.12353
|View full text |Cite
|
Sign up to set email alerts
|

Linking vitamin D status, executive functioning and self‐perceived mental health in adolescents through multivariate analysis: A randomized double‐blind placebo control trial

Abstract: The aim of the present randomized double-blind placebo control trial was to investigate if vitamin D supplementation had an effect on vitamin D status, executive functioning and self-perceived mental health in a group of Norwegian adolescents during winter time. Fifty adolescents were randomly assigned into an intervention group (vitamin D pearls) or a control group (placebo pearls). Before (pre-test in December/January) and after (post-test in April/May) the intervention period the participants were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Moreover, our results emphasize the TSH role in strengthening the relationship between glycemia and workers’ capacity to develop their work while they are sick. The present findings also contribute to the literature by considering the negative impact that high blood glucose has on individuals’ cognitive functions and job performance [ 18 , 38 ] and by showing that high levels of TSH moderate these effects. Thus, the current results indicated that high TSH may increase the detrimental effects of high glycemia on workers’ capacity to perform their tasks.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, our results emphasize the TSH role in strengthening the relationship between glycemia and workers’ capacity to develop their work while they are sick. The present findings also contribute to the literature by considering the negative impact that high blood glucose has on individuals’ cognitive functions and job performance [ 18 , 38 ] and by showing that high levels of TSH moderate these effects. Thus, the current results indicated that high TSH may increase the detrimental effects of high glycemia on workers’ capacity to perform their tasks.…”
Section: Discussionsupporting
confidence: 74%
“…Two of the studies included in the qualitative review were excluded from quantitative analysis because they did not report sufficient data and the corresponding authors could not be contacted. The 25 trials included in the meta‐analysis were conducted in Australia (4 trials: Dean et al, 2011; Lansdowne & Provost, 1998; Mousa, Naderpoor, de Courten, & de Courten, 2018; Sanders et al, 2011), Iran (8 trials: Alavi et al, 2018; Ghaderi et al, 2017; Jamilian et al, 2018; Khoraminya et al, 2013; Mozaffari‐Khosravi, Nabizade, Yassini‐Ardakani, Hadinedoushan, & Barzegar, 2013; Raygan, Ostadmohammadi, Bahmani, & Asemi, 2018; Sepehrmanesh et al, 2016; Vaziri et al, 2016), Norway (4 trials: Grung et al, 2017; Jorde & Kubiak, 2018; Jorde et al, 2008; Kjaergaard et al, 2012), United States (4 trials: Arvold et al, 2009; Bertone‐Johnson et al, 2012; Mason et al, 2016; Yalamanchili & Gallagher, 2012), Denmark (1 trial: Frandsen, Pareek, Hansen, & Nielsen, 2014), China (1 trial: Wang et al, 2016), Netherlands (1 trial: Rolf et al, 2017), Sweden (1 trial: von Berens et al, 2018), and New Zealand (1 trial: Choukri, Conner, Haszard, Harper, & Houghton, 2018). Sample size ranged from 34 to 726.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies included in the qualitative review were excluded from quantitative analysis because they did not report sufficient data and the corresponding authors could not be contacted. The 25 trials included in the meta-analysis were conducted in Australia (4 trials: Dean et al, 2011;Lansdowne & Provost, 1998;Mousa, Naderpoor, de Courten, & de Courten, 2018;Sanders et al, 2011), Iran (8 trials: Alavi et al, 2018;Ghaderi et al, 2017;Jamilian et al, 2018;Khoraminya et al, 2013;Mozaffari-Khosravi, Nabizade, Yassini-Ardakani, Hadinedoushan, & Barzegar, 2013;Raygan, Ostadmohammadi, Bahmani, & Asemi, 2018;Sepehrmanesh et al, 2016;Vaziri et al, 2016), Norway (4 trials: Grung et al, 2017;Jorde & Kubiak, 2018;Jorde et al, 2008;Kjaergaard et al, 2012)…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…Before vitamin D supplementation, the general mean status of 25-hydroxyvitamin D was 42 nmol/L, and after supplementation, the average was 62 nmol/L). Also, the group that received vitamin D supplementation improved their performance in the most demanding subtasks of ToH [19].…”
Section: Main Clinical Studies Systematic Reviews and Meta-analysis -Last 3 Yearsmentioning
confidence: 94%